2023
DOI: 10.1590/1678-4685-gmb-2022-0291
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA MALAT1 is upregulated in urine of type 1 diabetes mellitus patients with diabetic kidney disease

Abstract: Long non-coding RNAs (lncRNAs) are RNAs with >200 nucleotides that are unable to encode proteins and are involved in gene expression regulation. LncRNAs have a key role in many physiological and pathological processes and, consequently, they have been associated with several human diseases, including diabetes chronic complications, such as diabetes kidney disease (DKD). In this context, some studies have identified the dysregulation of the lncRNAs MALAT1 and TUG1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…They also reported that MALAT1 expression levels were correlated with ACR, urine β2microglobulin, urine α1-microglobulin, and creatinine (69). Recent studies have shown that the expression levels of MALAT1 are increased in the urine samples of type 1 diabetes patients with diabetic kidney disease (21).…”
Section: Diagnostic Role Of Malat1 As In Dnmentioning
confidence: 94%
See 1 more Smart Citation
“…They also reported that MALAT1 expression levels were correlated with ACR, urine β2microglobulin, urine α1-microglobulin, and creatinine (69). Recent studies have shown that the expression levels of MALAT1 are increased in the urine samples of type 1 diabetes patients with diabetic kidney disease (21).…”
Section: Diagnostic Role Of Malat1 As In Dnmentioning
confidence: 94%
“…In addition, a large number of studies have shown that cell-free ncRNAs have been dysregulated in the serum, plasma, urine, and peripheral blood samples of patients with T2D (17)(18)(19)(20). The metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), also termed nuclear enriched abundant transcript 2 (NEAT2), is one of the ncRNAs in human disease that has received the most attention from researchers, especially in diabetes and diabetic-related complications (21,22). In this study, the primary emphasis is placed on the functions that MALAT1 plays in relation to the pathophysiology of DN as well as the processes that underlie these roles.…”
Section: Introduction Dmentioning
confidence: 99%
“…Diabetes mellitus, distinguished by persistent high blood sugar due to compromised insulin function or secretion, poses a worldwide health challenge with increasing occurrence ( Chen et al, 2021 , Bhat et al, 2023a , Bhat et al, 2023b , Bhat et al, 2023c ). The complex interaction between genetic susceptibility and external elements contributes to the emergence of diabetes and its wide array of difficulties, spanning from cardiovascular ailments and kidney issues to retinal and nerve-related problems ( Dieter et al, 2023a , Dieter et al, 2023b ). Among the emerging players in this multifaceted landscape, lncRNAs have garnered significant consideration for the roles they play in regulation within gene expression, particularly the lncRNA TUG1 (taurine-upregulated gene 1), and their potential as epigenetic modulators in diabetes and diabetic associative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Among the emerging players in this multifaceted landscape, lncRNAs have garnered significant consideration for the roles they play in regulation within gene expression, particularly the lncRNA TUG1 (taurine-upregulated gene 1), and their potential as epigenetic modulators in diabetes and diabetic associative diseases. TUG1, initially recognized as a transcript increased by taurine treatment in retinal cells, has been implicated in diverse cellular processes through its involvement in epigenetic regulation ( Duan et al, 2017 , Dieter et al, 2023a , Dieter et al, 2023b ). Although initially linked to retinal development and function, subsequent studies have revealed its broader implications in various biological contexts, including cancer, neurodegeneration, and, more recently, diabetes ( Bhat et al, 2022a , Bhat et al, 2022b , Bhat et al, 2022c , Esawy et al, 2022a , Esawy et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%